2020
DOI: 10.1002/mnfr.201901238
|View full text |Cite
|
Sign up to set email alerts
|

Triacylglycerol‐Rich Oils of Marine Origin are Optimal Nutrients for Induction of Polyunsaturated Docosahexaenoic Acid Ester of Hydroxy Linoleic Acid (13‐DHAHLA) with Anti‐Inflammatory Properties in Mice

Abstract: Scope The docosahexaenoic acid ester of hydroxy linoleic acid (13‐DHAHLA) is a bioactive lipid with anti‐inflammatory properties from the family of fatty acid esters of hydroxy fatty acids (FAHFA). Methods and results To explore the biosynthesis of 13‐DHAHLA from dietary oils, C57BL/6N mice are gavaged for 8 days with various corn oil/marine oil mixtures containing the same amount of DHA. Plasma levels of omega‐3 FAHFAs are influenced by the lipid composition of the mixtures but do not reflect the changes in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 43 publications
0
39
0
Order By: Relevance
“…Multiple additional FAHFAs are also biologically active and have anti-diabetic (Benlebna et al, 2020a) and anti-inflammatory effects (Kolar et al, 2019;Paluchova et al, 2020), as well as other beneficial effects such as improving cognition in obese mice (Wen et al, 2020). The abundance of PAHSA isomers is reduced in WAT and serum of AdChREBP knockout (KO) mice, and 9-PAHSA supplementation completely reverses their insulin resistance (Vijayakumar et al, 2017).…”
Section: De Novo Lipogenesismentioning
confidence: 99%
“…Multiple additional FAHFAs are also biologically active and have anti-diabetic (Benlebna et al, 2020a) and anti-inflammatory effects (Kolar et al, 2019;Paluchova et al, 2020), as well as other beneficial effects such as improving cognition in obese mice (Wen et al, 2020). The abundance of PAHSA isomers is reduced in WAT and serum of AdChREBP knockout (KO) mice, and 9-PAHSA supplementation completely reverses their insulin resistance (Vijayakumar et al, 2017).…”
Section: De Novo Lipogenesismentioning
confidence: 99%
“…Surprisingly, both studied FAHFAs induced hepatic steatosis and fibrosis in some mice, which were more marked with 9-PAHPA. Again, in mice, dietary triacylglycerol-rich oils of marine origin were identified as optimal nutrients for the induction 13-DHAHLA exhibiting anti-inflammatory properties [38].…”
Section: Biological Relevancementioning
confidence: 99%
“…FAHFAs are a novel class of bioactive lipid, forming by esteri cation hydroxyl group of a hydroxy fatty acid and the carboxyl group of a fatty acid [50]. Previous studies have shown that palmitic acid esters of hydroxy stearic acids and the family of polyunsaturated FAHFAs have antiin ammatory and immunomodulatory effects [51,52]. Besides, several new short-chain FAHFAs (SFAHFAs) of acetic acid or propanoic acid esteri ed long-chain hydroxy fatty acids tended to be lower in mice fed with a high-fat diet than those fed with a regular diet [53].Similarly, STA treatment decreased the concentrations of several SFAHFAs like FAHFA (2:0/24:2) and FAHFA (4:0/22:0) during the withdrawal period, which coincided with higher content of body lipid and lower abundance of Blautia, a bacterium with a protective role against obesity.…”
Section: Discussionmentioning
confidence: 99%